2020
DOI: 10.3389/fendo.2020.00233
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-1 Expression Promotes Tamoxifen Resistance in Breast Cancer Cells via Erk Pathway Activation

Abstract: Insulin-like growth factor (IGF) system plays a significant role in many cellular processes, including proliferation, and survival. In estrogen receptor positive breast cancer, the level of circulating IGF-1 is positively associated with the incidence and at least 50% of cases have elevated IGF-1R signaling. Tamoxifen, a selective estrogen receptor modulator and antagonist for estrogen receptor alpha (ERα) in breast tissue, is a commonly prescribed adjuvant treatment for patients presenting with ERα-positive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…MMP1 has also been shown to crosstalk with the IGF pathway by degrading IGFBP-1 that binds IGF with high affinity. Elevated IGFBP-1 expression has been reported in tamR MCF-7 and T-47D breast cancer cells, suggesting an association between tam resistance and IGFBP-1 accumulation [ 41 ]. Second, MMP1 might induce tam resistance by acting independently through previously identified routes including ER, EGF, or IGF pathways.…”
Section: Discussionmentioning
confidence: 99%
“…MMP1 has also been shown to crosstalk with the IGF pathway by degrading IGFBP-1 that binds IGF with high affinity. Elevated IGFBP-1 expression has been reported in tamR MCF-7 and T-47D breast cancer cells, suggesting an association between tam resistance and IGFBP-1 accumulation [ 41 ]. Second, MMP1 might induce tam resistance by acting independently through previously identified routes including ER, EGF, or IGF pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a few unique proteins in WM but not in MGUS samples, including IGFBP1, TFRC and Hemicentin 2 (HMCN2). Previous data have reported increased expression of IGFBP1 and its association with an elevated risk of prostate or pancreatic cancer [ 29 , 30 ] or resistance to therapy in breast cancer [ 31 ]. While TFRC is associated with iron metabolism and anemia [ 32 ], the presence of TFRC in the serum of the patients with Hodgkin or non-Hodgkin's lymphoma is shown to correlate with disease severity rather than iron-deficiency anemia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through a genome-wide RNA interference screen, IGFBP1 was identified as one of the novel genes causing cellular resistance to neratinib [ 45 ]. Molecular mechanistic understanding has revealed that IGFBP1 is a key component of G protein-coupled estrogen receptor 1 (encoded by GPER1 ) which regulated the sensitivity of breast cancer cells to tamoxifen [ 46 , 47 ], and the resistance induced by RG7388 (MDM2 inhibitor) in glioblastoma [ 48 ]. Another study showed that reduction in insulin-like growth factor I (encoded by IGF-I ) mediated part of the starvation-dependent differential stress resistance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%